Analisis Wacana Keagamaan Perspektif Teologi Skizofrenia - Setiyani, Wiwik (Religió: Jurnal Studi Agama-agama, 2011)
The threat for humanism and fanaticism is an important issue which needs more attention from all religious thinkers. The opinion which is given by religious person and intellectuals, is the ideology that is created in order to be able to play role as decision maker. Theology of schizophrenia is a new discourse, especially in the religious discourse and has sharp implication in discussing action. Theology of schizophrenia offers four aspects as basic ideas on religious discourses: intellectual, ideological, technology, and religious aspect. These aspects are complementing and holistically connected. Generally, the theology of schizophrenia intends to explore basic concept of human conflict. To apply this concept into religious discourses, we need comprehensive instrument in order to dissociate people anarchy. One of the important things that we should concern is the strategy and method of its application. The theology of schizophrenia established its methodology on the knees of religious values. It could be applied as a standard to measure good or bad things. Theology of schizophrenia will be positive if it ontologically relates to religious values and axiologically produce humanistic meanings.